The Validity of Reconciliation Following A Single Bain Sughra Divorce According to The Sharia Court And A Third Divorce According to Islamic Law, As Well As The Legal Consequences for The Child - Muhammad Naufal; Ilyas Yunus; Mukhlis Mukhlis (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The difference in the determination of when a divorce takes effect between Islamic law and statutory law raises issues in the judicial practice of the Sharia Court. In a number of cases, judges have issued a single bain sughra divorce even though, according to Sharia law, the husband has already issued three divorces. This raises issues regarding the validity of reconciliation and its legal implications for the status of the children. This study aims to analyze the differences in the concept of divorce, the reasons for the judges’ decisions, the validity of reconciliation, and the legal consequences for children in both legal systems. This study employs a mixed-methods approach (normative and empirical) using legislative, conceptual, and comparative frameworks. The analysis is conducted through comparative theory, legal certainty, maqāṣid al-syarī’ah, and child protection. The results indicate a fundamental difference between substantive validity in Islamic law and formal validity in positive law. The Sharia Court’s ruling on a single bain sughra divorce is based on procedural caution, yet it creates a dualism regarding the validity of reconciliation and the potential for legal uncertainty. Regarding children, positive law provides full recognition, while Islamic law continues to emphasize the caution regarding lineage but is oriented toward protecting the best interests of the child. This study offers an integrative approach by recognizing out-of-court divorce as a substantive legal fact to bridge legal certainty and justice.